Możliwości zapobiegania agresywnemu planowaniu finansowemu - Hybka, Małgorzata Magdalena (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
Tax planning strategies are growing more and more sophisticated over time. Formany OECD member states, these strategies applied by multinational corporationsresult in an immense loss of tax revenue. Therefore counteracting aggressive taxplanning has become a priority of tax policy for both the OECD and the EuropeanUnion. The aim of this article is to analyze selected aggressive tax planning schemes.It also presents definition of aggressive tax planning, reviews its instruments andscale. Moreover it indicates and describes the means to combat aggressive tax planning, such as transfer pricing regulations, institution of controlled foreigncorporation, general anti avoidance rules and thin capitalization provisions.